The Effect of Authoritarian Parenting Styles on Identity Crisis Among High School Students - Muhazir; Risa Agustiana (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
Parents who are overly strict in enforcing rules and exercising control can trigger role confusion and hinder adolescents’ process of self-exploration. This study aims to examine the influence of authoritarian parenting on identity crises among high school students. This study employs a quantitative approach using a simple linear regression design. The study participants consisted of 36 students aged 16–17 years, all 11th-grade students, selected using proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire. Data analysis was conducted using SPSS 25. The results indicate that authoritarian parenting has a positive and significant effect on identity crisis, accounting for 71.6% of the variance. These results indicate that the higher the level of authoritarian parenting, the higher the tendency for students to experience an identity crisis. These findings underscore the importance of evaluating parental parenting styles to minimize the risk of psychosocial developmental barriers and to support the formation of a more mature adolescent identity within the school environment.